THE DISTRIBUTION OF SOFT TISSUE SARCOMA BASED ON HISTOPATHOLOGY’S CHECK IN PEKANBARU’S HOSPITAL BETWEEN 2009-2013 - Wilda Arfiana; Laode Burhanuddin; Wiwit Ade Fidiawati (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTThe disease pattern which caused mortality today is switchover from communicable disease to non-communicable disease, including the disease which caused malignancy. Malignancy case is in the second list after cardiovascular disease. One of the malignancy cases that often happen is soft tissue sarcoma. Based on estimation data, the number of the new case and mortality number by cancer in Dharmais Hospital in Jakarta 2012-2013, soft tissue sarcoma is the top 10 cancer caused. The aim of this research is knowing the distribution of soft tissue sarcoma in Pekanbaru’s Hospital between 2009-2013 based on histopathology check examination, age and sex. This research is using descriptive method, cross-sectional type. The data is taken from histopathology answer check sheet in center of diagnostic anatomical pathology laboratory and from hospitals in Pekanbaru. The result shows that the number of soft tissue sarcoma is about 195 cases. The most case happens in Arifin Achmad general hospital Riau Province which reaches about 116 cases. Soft tissue sarcoma most found in female (60%) than male. The age is between 40-49 years old, meanwhile histopathology’s type that often found is rhabdomyosarcoma, it is about 17,9%.Key words : soft tissue sarcoma, distribution, histopathology’s type